MPROVING LISTENING AND SPEAKING SKILLS AMONG TECHNICAL COLLEGE STUDENTS IN ENGLISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores methods for improving listening and speaking skills among technical college students learning English. Listening and speaking are essential components of language acquisition, enabling students to communicate effectively in academic and professional settings. The study highlights interactive teaching strategies, such as role-play, group discussions, and multimedia resources, to enhance oral communication and comprehension. The article emphasizes two main focus areas: developing effective listening strategies and promoting confident speaking in real-life situations. Practical recommendations for educators are also provided